2020
DOI: 10.1101/2020.11.16.384818
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Divergent profiles of fentanyl withdrawal and associated pain in mice and rats

Abstract: Opioid abuse has devastating effects on patients, their families, and society. Withdrawal symptoms are severely unpleasant, prolonged, and frequently hinder recovery or lead to relapse. The sharp increase in abuse and overdoses arising from the illicit use of potent and rapidly-acting synthetic opioids, such as fentanyl, highlights the urgency of understanding the withdrawal mechanisms related to these drugs. Progress is impeded by inconsistent reports on opioid withdrawal in different preclinical models. Here… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 72 publications
(75 reference statements)
2
2
0
Order By: Relevance
“…We show here that the injection of NLX elicited pronounced withdrawal syndrome consisting of behavioral and cardiorespiratory responses, and falls in body temperature and body weight, in male rats that received twice-daily co-injections of fentanyl (125 μg/kg, IV) + vehicle. These withdrawal phenomena seen in this study are strongly suggestive of the rats having become physically-dependent on fentanyl, and are consistent with reports on the patterns of NLXprecipitated withdrawal signs seen in a variety of fentanyladministration protocols (Bartoletti et al, 1987;Adams and Wooten, 1994;De Kock and Meert, 1995;Thornton and Smith, 1997;Fendt and Mucha, 2001;Lohmann and Smith, 2001;Chen and Pan, 2006;Bruijnzeel et al, 2007;Liu et al, 2008;Mitzelfelt et al, 2011;Mitzelfelt et al, 2014;Gyawali et al, 2020;Uddin et al, 2021), and in other protocols used to induce physical dependence to opioids (Laska et al, 1976;Laska et al, 1977;Hutchinson et al, 2007;Lopez-Gimenez and Milligan, 2010;Morgan and Christie, 2011;Nielsen and Kreek, 2012). Moreover, the lack of behavioral responses elicited by the injection of NLX in rats that received co-injections of vehicle + vehicle, vehicle + D-CYSee or vehicle + D-CYSea suggests that the behavioral phenomena that occurred upon the injection of NLX in fentanyl-injected rats were indeed withdrawal phenomena (due to the development of physical dependence to the opioid), rather than other potential issues (e.g., multiple injection protocols) that would lead NLX to cause behavioral reactions.…”
Section: Discussionsupporting
confidence: 91%
“…We show here that the injection of NLX elicited pronounced withdrawal syndrome consisting of behavioral and cardiorespiratory responses, and falls in body temperature and body weight, in male rats that received twice-daily co-injections of fentanyl (125 μg/kg, IV) + vehicle. These withdrawal phenomena seen in this study are strongly suggestive of the rats having become physically-dependent on fentanyl, and are consistent with reports on the patterns of NLXprecipitated withdrawal signs seen in a variety of fentanyladministration protocols (Bartoletti et al, 1987;Adams and Wooten, 1994;De Kock and Meert, 1995;Thornton and Smith, 1997;Fendt and Mucha, 2001;Lohmann and Smith, 2001;Chen and Pan, 2006;Bruijnzeel et al, 2007;Liu et al, 2008;Mitzelfelt et al, 2011;Mitzelfelt et al, 2014;Gyawali et al, 2020;Uddin et al, 2021), and in other protocols used to induce physical dependence to opioids (Laska et al, 1976;Laska et al, 1977;Hutchinson et al, 2007;Lopez-Gimenez and Milligan, 2010;Morgan and Christie, 2011;Nielsen and Kreek, 2012). Moreover, the lack of behavioral responses elicited by the injection of NLX in rats that received co-injections of vehicle + vehicle, vehicle + D-CYSee or vehicle + D-CYSea suggests that the behavioral phenomena that occurred upon the injection of NLX in fentanyl-injected rats were indeed withdrawal phenomena (due to the development of physical dependence to the opioid), rather than other potential issues (e.g., multiple injection protocols) that would lead NLX to cause behavioral reactions.…”
Section: Discussionsupporting
confidence: 91%
“…Each of these behaviors were greatest at the beginning of the observation period and waned by 3-4h, where the duration of the increases in each behavior was dose-dependent. These behaviors are similar to that observed in rodents and pigs following abstinence (Varshneya et al, 2019;Digranes et al, 2023) or naloxone-precipitated withdrawal from fentanyl (Uddin et al, 2021), suggesting that the adult goat may also be a useful model to study mechanisms or other unique aspects of withdrawal from fentanyl and its relevance to human withdrawal symptomatology.…”
Section: Discussionsupporting
confidence: 64%
“…Studies have also reported that withdrawal behavior can vary from protocols investigating precipitated or spontaneous withdrawal [59]. Evaluating animals in observation chambers, for instance, is one factor that can play a role in the differences in withdrawal behavior, as space constraint might limit the number of wet dog shakes, abdominal constrictions and writhing behavior observed during a determined time of testing [58]. In addition, jumping behavior might be impacted by the height of observation chambers, as rats in withdrawal have shown to jump less as the height of the chamber increases [60].…”
Section: Discussionmentioning
confidence: 99%
“…Precipitated withdrawal behavior can be expressed in humans and laboratory animals as affective and emotional symptoms, as well as somatic signs. A spectrum of behavior occurs in both rats and mice in a similar manner, as shown by only few studies that investigated potential differences between species[58]. Studies have also reported that withdrawal behavior can vary from protocols investigating precipitated or spontaneous withdrawal[59].…”
Section: Discussionmentioning
confidence: 99%